Pewarna Alami Ekstrak Biji Pinang (Areca catechu L.) Pada Sediaan Pelembab Bibir Dengan Kombinasi Basis Minyak - Budi Sawitri, Satwika; Mahardika, Muladi Putra; Sholikhah, Anggun Mahirotun Nur; Madaniah, Stevania Bunga (Universitas Muhammadiyah Klaten, 2025)
As we get older, the structure and quality of the lips begin to change a lot. Starting from the appearance of fine lines to wrinkles on the upper and lower lips. The influence of climate and weather also causes a lot of damage to the lip lining, making the lips dry and chapped. One preparation that can be used to treat lip problems is lip moisturizer. Nowadays, besides the benefits of lip moisturizer to maintain or reduce the evaporation of water in the lip area, it can also be used at the same time to give color to the lips to make them look prettier. The oil phase content in lip moisturizer preparations also plays a role in maintaining lip moisture. Based on this, the research aims to make a lip moisturizer preparation with natural dyes from Areca nut (Areca catechu L.) extract with a combination of an oil phase base as an emollient as well as a moisturizer for the lips. This research method is an experimental research design with variations in the concentration of Areca nut extract as a natural dye and a combination of oil bases, namely canola oil and olive oil. The result of the evaluation quality of the lip balm preparation in the organoleptic test showed that the preparation had a semi-solid consistency with a dark red-brown color and a distinctive smell of coffee essence. The preparation shows a homogeneous composition, with a pH value in the range of 6.1-6.6. The spreadability of the preparation ranges from a diameter of 6.2-6.9 cm, with the melting point showing a temperature range between 50-64 °C. Based on the result of the evaluation quality of the lip moisturizer preparation it has met the standard requirements for the quality of the preparation. So it can be concluded that Areca nut (Areca catechu L.) extract can be used as a natural dye in the lip balm preparations with a stable color consistency and the use of a combination of canola oil and olive oil for bases able to maintain moisture on the lips.